Singing Social Inclusion: Towards the Applicability of German Approaches to Community Building in Australian Choral Music - Leske, Benjamin (Voices: A World Forum for Music Therapy, 2016)
Germany is a country with a proud musical heritage. Music making in community is Germany’s largest civic activity and there are a vast number of active choirs and choral organisations. Choral singing is valued as a cultural asset and national export. In this article I survey the recent history of choral singing in Germany, a civic movement that is expanding and changing beyond traditional understandings of what it means to be a “choir” and with evolving organisational structures supporting its growth. This article summarises findings of a larger 2014 study undertaken for the Australian German Association (AGA) and the Goethe Institut. It offers a number of suggestions for colleagues, leaders, and policy-makers who work in choral music in Australia, a country with a vibrant choral music scene but with much potential to improve its supporting institutional structures. As a community music research project, it may provide wider context for music therapists with an interest in community music therapy in particular. This article was first published in Sing Out (Vol. 32, No. 2, 2015)[1] and is adapted here to share my experiences and findings beyond Australia’s choral music community.